If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + -1y)(3y + 7) = 0 Reorder the terms: (8 + -1y)(7 + 3y) = 0 Multiply (8 + -1y) * (7 + 3y) (8(7 + 3y) + -1y * (7 + 3y)) = 0 ((7 * 8 + 3y * 8) + -1y * (7 + 3y)) = 0 ((56 + 24y) + -1y * (7 + 3y)) = 0 (56 + 24y + (7 * -1y + 3y * -1y)) = 0 (56 + 24y + (-7y + -3y2)) = 0 Combine like terms: 24y + -7y = 17y (56 + 17y + -3y2) = 0 Solving 56 + 17y + -3y2 = 0 Solving for variable 'y'. Factor a trinomial. (8 + -1y)(7 + 3y) = 0Subproblem 1
Set the factor '(8 + -1y)' equal to zero and attempt to solve: Simplifying 8 + -1y = 0 Solving 8 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 0 + -8 -1y = 0 + -8 Combine like terms: 0 + -8 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8Subproblem 2
Set the factor '(7 + 3y)' equal to zero and attempt to solve: Simplifying 7 + 3y = 0 Solving 7 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3y = 0 + -7 3y = 0 + -7 Combine like terms: 0 + -7 = -7 3y = -7 Divide each side by '3'. y = -2.333333333 Simplifying y = -2.333333333Solution
y = {8, -2.333333333}
| 5t^2=7t | | 3x^3+4x-32=0 | | 4(w-3)(-w+2)=0 | | 3x^3-4x-32=0 | | 27x^2-26=0 | | 6+2t-1=5t+12-2t | | 5(4x)=125(x+7) | | X+3*5=28 | | 22.8-2p=44.4 | | -15z-15=2z-8 | | 6v+5t+8v+2t= | | 5+4t-1=8t+14-4t | | 3x-6=x-2 | | (3z+4)(7-z)=0 | | (y+7)(y-1)=0 | | 8x^2-2x+3=0 | | -15+15w=6w-4 | | 5t-3-t+2= | | 25x^2-200x=0 | | 6n+6=3n+9 | | 4x^2-8x+11=0 | | x^2+7x=10 | | 40=10(x+7) | | (3z+2)(1-z)=0 | | 2x+3-3x+9= | | (3z+2)(1-x)=0 | | 7t^2+2t=0 | | -16t^2+109t+90=0 | | 9x+2-2= | | (y+7)(y+6)=0 | | r^4-49= | | 3x^3+6x^2-24=0 |